Biotransformation of the Pentahydroxy Flavone Quercetin by Rhizobium loti and Bradyrhizobium Strains (Lotus) - Rao, J. R. (1991)
Lotus rhizobia catabolized quercetin in an arabinose-based medium via a novel form of C-ring cleavage, yielding phloroglucinol and protocatechuic acid. Conservation of the A and B rings of the flavone suggests that a chalcone could be formed as a transient intermediate.